Metafora “Pasang Ri Kajang” Sebagai Perwujudan Budaya Lokal Masyarakat Kajang (International Forum of Researchers and Lecturers, 2023)
The purpose of this study is to describe the types of metaphors, namely, anthropomorphic, animalistic, and synesthetic as well as the meaning in the text of the ri Kajang tide as the embodiment of the local culture of the Kajang people. This research was conducted for about two months in the Kajang Ammatoa Area, Bulukumba Regency. This research is a research with a qualitative approach. Based on the results of the analysis and discussion of the use of figurative language in the text of the ri Kajang tide, it can be concluded that the results of this study indicate that there are various forms of figurative language found in the text of the ri Kajang ri. contained in the text of the tide ri kajang. The findings related to figurative language metaphor and the meaning of the text of the ri kajang pair are as many as 13 data. There are four data of anthropomorphic metaphors, five data of animal metaphors, and four data of synesthetic metaphors.